(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Obstetric brachial plexus injury (OBPI) can lead to long-term shoulder sequelae, especially in infants with upper trunk (C5–C6/7) palsy. Historically, shoulder deformities from OBPI were managed with open releases and tendon transfers (e.g. the Sever–L’Episcopo procedure). Recent decades have seen the emergence of arthroscopic techniques to treat internal rotation contractures and glenohumeral dysplasia in OBPI. Methods: We review the evolution of OBPI shoulder management, focusing on arthroscopic interventions in infants and adolescents. Key surgical techniques (arthroscopic contracture release, tendon transfers, etc.), their outcomes relative to open surgery, rehabilitation protocols, pediatric-specific considerations, and future innovations are discussed. Results: Arthroscopy allows minimally invasive release of contracted subscapularis and capsule, often restoring external rotation and improving glenohumeral alignment. Combined arthroscopic release and tendon transfer (latissimus dorsi ± teres major) yields significant gains in shoulder abduction and external rotation function. Studies report improved Mallet functional scores and glenoid remodeling in many patients after arthroscopic procedures. Compared to traditional open surgery, arthroscopy achieves comparable or superior shoulder motion with smaller incisions and potentially fewer complications. Conclusions: Arthroscopic management of OBPI shoulder sequelae has advanced the field by enabling early joint-centered interventions in infants and effective minimally invasive reconstructions in older children. Optimal outcomes require careful patient selection, precise technique adapted to pediatric anatomy, and structured rehabilitation. Continued innovations – including refined arthroscopic methods, muscle-sparing releases, and novel tendon transfer options – promise further improvements in treating OBPI shoulder deformities.